Surgical Resection Followed by Stereotactic Radiosurgery (S+SRS) Versus SRS Alone for Large Posterior Fossa Brain Metastases: A Comparative Analysis of Outcomes and Factors Guiding Treatment Modality Selection - Ruth Lau; Enrique Gutierrez-Valencia; Anna Santiago; Carolyn Lai; Danyal Baber Ahmed; Parnian Habibi; Normand Laperriere; Tatiana Conrad; Barbara-Ann Millar; Mark Bernstein; Paul Kongkham; Gelareh Zadeh; et al. (Brain Sciences)
Background/Objectives: Around 20% of cancer patients will develop brain metastases (BrMs), with 15–25% occurring in the posterior fossa (PF). Although the effectiveness of systemic therapies is increasing, surgery followed by stereotactic radiosurgery (S+SRS) versus definitive SRS remains the mainstay of treatment. Given the space restrictions within the PF, patients with BrMs in this location are at higher risk of brainstem compression, hydrocephalus, herniation, coma, and death. However, the criteria for treating large PF BrMs with S+SRS versus definitive SRS remains unclear. Methods: We reviewed a prospective registry database (2009 to 2020) and identified 64 patients with large PF BrMs (≥4 cc) treated with SRS or S+SRS. Clinical and radiological parameters were analyzed. The two endpoints were overall survival (OS) and local failure (LF). Results: Patients in the S+SRS group were more highly symptomatic than patients in the SRS group. Gait imbalance and intracranial pressure symptoms were 97% and 80%, and 47% and 35% for S+SRS and SRS, respectively. Radiologically, there were significant differences in the mean volume of the lesions [6.7 cm3 in SRS vs. 29.8 cm3 in the S+SRS cohort, (p < 0.001)]; compression of the fourth ventricle [47% in SRS vs. 96% in S+SRS cohort, (p < 0.001)]; and hydrocephalus [0% in SRS vs. 29% in S+SRS cohort, (p < 0.001)]. Patients treated with S+SRS had a higher Graded Prognostic Assessment (GPA). LF was 12 and 17 months for SRS and S+SRS, respectively. Moreover, the S+SRS group had improved OS (12 vs. 26 months, p = 0.001). Conclusions: A higher proportion of patients treated with S+SRS presented with hydrocephalus, fourth-ventricle compression, and larger lesion volumes. SRS-alone patients had a lower KPS, a lower GPA, and more brain metastases. S+SRS correlated with improved OS, suggesting that it should be seriously considered for patients with large PF-BrM.